Design Smart Trash Based On the Inductive Proximity Sensor - Wulandari, Rindi; Ariwibowo, M. Riyad; Taryo, Taryo; Ananda, Galieh (PT. Riset Press International, 2024)
Smart waste management, including a waste sorting system based on type, strongly supports the